1992
DOI: 10.1007/bf00012813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the VAM fungus Glomus sp. on the growth and yield of soybean inoculated with Bradyrhizobium japonicum

Abstract: The effect of two Bradyrhizobium japonicum strains (D344 and Urbana), on the frequency and intensity of infection by a VAM fungal Glomus sp. and the effect of VAM on biomass production by nodulating plants were tested in soybean growing in a soil containing low levels of accessible P and N. During the initial stage of vegetative growth, mycorrhiza frequency in roots inoculated with the two rhizobial strains did not differ. However, during flowering it was 178% higher in roots with the strain D344 than in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…In general, results from these studies have shown that dual inoculation with AMF and rhizobia increase plant growth and N 2 fixation to a greater extent than inoculation with only one microorganism ( Vejsadova et al, 1992Vejsadova et al, , 1993George et al, 1995;Ibijbijen et al, 1992;Antunes et al, 2006a). As a consequence of the large number of studies already available, it is commonly accepted that there is a mutualistic tripartite symbiosis between AMF, rhizobia and legumes.…”
Section: Discussionmentioning
confidence: 97%
“…In general, results from these studies have shown that dual inoculation with AMF and rhizobia increase plant growth and N 2 fixation to a greater extent than inoculation with only one microorganism ( Vejsadova et al, 1992Vejsadova et al, , 1993George et al, 1995;Ibijbijen et al, 1992;Antunes et al, 2006a). As a consequence of the large number of studies already available, it is commonly accepted that there is a mutualistic tripartite symbiosis between AMF, rhizobia and legumes.…”
Section: Discussionmentioning
confidence: 97%
“…Trabalhando em solos de cerrado, Paula et al (1990) verificaram que diferentes populações de fungos micorrízicos mostraram diferenças na taxa de colonização, de absorção de P, de produção de matéria seca da parte aérea, e de produção de grãos da soja. Miranda et al (1989) mostraram que a inoculação de fungos micorrízicos no sorgo aumentou a produção de matéria seca da parte aérea e os teores de P e N. Na soja, além dos benefícios diretos, existem efeitos positivos na interação fungo micorrízico-rizóbio, que resultam da melhor nutrição de P, necessária para a nodulação e a fixação biológica de N (Paula & Siqueira, 1987;Vejsadova et al, 1992).…”
Section: Introductionunclassified
“…Given the dependence of the soybean-rhizobia symbiosis on phosphorus, this could be in part because coinoculation increases P availability much more than single inoculation (Bagyaraj et al 1979). This improvement in nodulation occurs primarily early in the season (Ganry et al 1985;Vejsadova et al 1992). Other earlyseason benefits of co-inoculation with G. mosseae and B. japonicum include emergence and seedling vigor (Alahdadi et al 2009).…”
Section: Vesicular-arbuscular Mycorrhizae (Vam)mentioning
confidence: 99%
“…Correa et al (2009) found that Bagyaraj et al 1979 Glomus fasciculatis field +48 % (60 days) +71 % (60 days) Asimi et al 1980 Glomus mosseae pot +193 % +140-177 % (46 days) Ganry et al 1985 Glomus mosseae field +114 % (26 days); N.S. (40 days) +28 % Harris et al 1985 Glomus fasciculatum pot +38 % (6 weeks); +86 % (9 weeks) +40 % (6 weeks); +86 % (9 weeks) Bethlenfalvay et al 1989 Glomus mosseae pot +118 % +320 % +100 % Hamel et al 1991 Glomus intradices field +55 % Vejsadova et al 1992 Glomus claroideum pot +162 % (7 weeks); +41 % (12 weeks) N.S. Inoculation with VAM improved nodule number and weight and nitrogen fixation in soybean.…”
Section: Interactions Of Vam and Pgprmentioning
confidence: 99%